FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN APLIKASI "PEDULILINDUNGI" DENGAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Juwita Andriani; Wing Wahyu Winarno (ZONAsi: Jurnal Sistem Informasi, 2022)
The Covid-19 pandemic that has spread in the country, especially Indonesia, has been going on for almost two years. At the beginning of 2020, the Covid-19 pandemic shocked the world, and the entire world population panicked over this pandemic. The Government of the Republic of Indonesia has made various efforts to deal with the spread of the Covid-19 virus, one of which is the use of information technology. In a pandemic situation, using digital communication is widely used by the community, so KEMKOMINFO and the Ministry of State-Owned Enterprises (BUMN) collaborate to create a mobile application called the "PeduliLindungi" application. This application can only be accessed via electronics such as smartphones, laptops, and others. The government has begun to require the use of the PeduliLindungi application for everyone who will be doing public space activities. The samples in this study were students, lecturers, civil servants, BUMN employees, private employees and others who were in Indonesia. This study uses a purposive sampling technique with user criteria using the PeduliLindung application. The results of the study prove that self-efficacy has a positive effect on perceived ease of use, self-efficacy has no effect on the use of the pedulilindungi application, subjective norm has a positive effect on perceived usefulness, subjective norm has a positive effect on the use of the pedulilindungi application, perceived ease of use has a positive effect on the use of the pedulilindungi application, perceived usefulness has a positive effect on the pedulilindung application. The test equipment in this study used warp-pls with 366 respondents.